[(-1)(-1)][(-1)(-1)](-1)=
[(1)(1)](-1)=
(1)(-1)=
......................(-1)
2006-11-20 09:37:54
·
answer #1
·
answered by merviedz trespassers 3
·
1⤊
0⤋
-1
2006-11-20 17:44:07
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
-1
2006-11-20 17:39:08
·
answer #3
·
answered by D C 2
·
1⤊
0⤋
It's -1. Multiply -1 by itself 5 times and see what happens!
2006-11-20 17:50:00
·
answer #4
·
answered by steiner1745 7
·
0⤊
0⤋
-1*-1*-1*-1*-1=-1
2006-11-20 17:43:31
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
It is -1
-1 to an odd exponent is negative one
-1 to an even exponent is positive one
This is because a negative times a negative is a positive, if you multiply a negative number by itself an odd number of times every two of the multiples will cancle each other out, and the one that is left over will make it negative again.
(-1)^1 = -1 = -1
(-1)^2 = (-1)*(-1) = 1
(-1)^3 = (-1)*(-1)*(-1) = -1
Similarly
(-3)^2 = (-3)*(-3) = 6
but
(-3)^3 = (-3)*(-3)*(-3) = -9
(-1)^208409829085929935 = (-1) (because the exponent is odd)
2006-11-20 17:45:22
·
answer #6
·
answered by iMi 4
·
0⤊
0⤋
-1...
Remember that the number is negative and the power is an odd number, you're always going to get a negative number for an answer.
As far as the 1, I don't think you'll have a problem multiplying 1 five times... right? =)
2006-11-20 17:46:29
·
answer #7
·
answered by Estrella 2
·
0⤊
0⤋
-1 raised to odd power is -1 and -1 raised to even power is +1
2006-11-20 17:42:16
·
answer #8
·
answered by raj 7
·
1⤊
0⤋
(-1)x(-1)x(-1)x(-1)x(-1)= -1
and you don't have to use a calculator.
2006-11-20 17:40:20
·
answer #9
·
answered by Anonymous
·
1⤊
0⤋
-1. use a calculator!!!
2006-11-20 17:38:59
·
answer #10
·
answered by stitchfan85 6
·
1⤊
0⤋